Application of fat meal in thoracic duct outlet obstruction reconstruction surgery - Yingying Jiang; Zhichao Yao; Dayong Zhou; Zhanao Liu (BMC Surgery)
Abstract Background To investigate the effectiveness and safety of preoperative fat meal administration in patients undergoing thoracic duct reconstruction for chylous leakage due to thoracic duct outlet obstruction. Methods A retrospective study was conducted on 18 patients diagnosed with thoracic duct outlet obstruction who underwent thoracic duct reconstruction between January 2022 and August 2024. Patients were administered a fat meal before surgery. The time interval between ingesting the fat meal and the exposure of the thoracic duct was recorded. Additionally, the appearance of the thoracic duct, the operating time duration, and any injuries to the thoracic duct or lymphatic branches were recorded. Results 11 patients’ thoracic ducts were exposed within 6–8 h after the fat meal, of which nine patients exhibited a milky white thoracic duct. The average surgical duration was 126.82 ± 53.30 min, and no injuries to the thoracic duct or its branches occurred in these patients. Additionally, seven patients’ thoracic ducts were exposed more than eight hours after a fat meal, among which only three patients had a milky white appearance of the thoracic duct. The average surgical duration for these patients was 180.00 ± 48.31 min ( P < 0.05), and injuries to the thoracic duct and its branches occurred in two patients. All patients achieved favourable therapeutic outcomes after thoracic duct reconstruction surgery. Conclusion Preoperative fat meals appear to enhance intraoperative visualization of the cervical segment of the thoracic duct during reconstructive surgery for thoracic duct obstruction, potentially contributing to reduced operative times and decreased incidence of iatrogenic thoracic duct injuries.